2021
DOI: 10.15294/jpii.v10i4.32386
|View full text |Cite
|
Sign up to set email alerts
|

Green Organizational Culture and Organizational Performance: The Mediating Role of Green Innovation and Environmental Performance

Abstract: This study aims to develop and test a theoretical model that empirically examines how green organizational culture affects organizational performance. Additionally, investigated and statistically explored the study model's and their mediating role of environmental performance and green innovation, which had previously received little attention. For the sample size of 170 respondents, a quantitative approach was used. In addition, convenient random sampling was utilized to get data from the respondents. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 72 publications
1
16
0
3
Order By: Relevance
“…GI is noted as a significant factor in green aspects. In Malaysian industries, EP and GI appear as full mediators that develop the relationships between firm performance and green OEC [71]. In his study, Wang [41] targets manufacturing firms to assess corporate green culture and green performance.…”
Section: Mediating Effect Of Gimentioning
confidence: 99%
See 1 more Smart Citation
“…GI is noted as a significant factor in green aspects. In Malaysian industries, EP and GI appear as full mediators that develop the relationships between firm performance and green OEC [71]. In his study, Wang [41] targets manufacturing firms to assess corporate green culture and green performance.…”
Section: Mediating Effect Of Gimentioning
confidence: 99%
“…Consequently, in its capacity as a mediating variable, GI has a good reputation for developing the associations between the different factors [41,50,71]. However, the integration of ES and EP remains untested.…”
Section: Mediating Effect Of Gimentioning
confidence: 99%
“…The environmental performance focuses on the organizational actions that go beyond primary compliance with basic rules and regulations to meet and exceed social expectations about the natural environment [67][68][69]. It involves the environmental impacts of organizational operations, products, and resource use in the most compliant way possible with applicable environmental laws [70].…”
Section: Green Innovation and Environmental Performancementioning
confidence: 99%
“…According to statistical definitions, discriminant validity is a circumstance in which a study evaluates two statistically distinct elements [67]. To evaluate discriminant validity, first compute the square roots of AVE and then compare them to the correlations of both of these variables in the theoretical model [128].…”
Section: Plos Onementioning
confidence: 99%
“…Meanwhile, according to Nishant et al (2012) andEl-Kassar &Singh (2019), there is little evidence in it of the relationship between green innovation and organizational performance. Furthermore, research has shown that green innovation is critical to achieving long-term performance (Cloud et al, 2019;Imran et al, 2021). According to Agustia et.…”
Section: Introductionmentioning
confidence: 99%